Exploring diversity rock-inhabiting fungi from northern Thailand: a new genus and three new species belonged to the family Herpotrichiellaceae - Thitla, Tanapol; Kumla, Jaturong; Hongsanan, Sinang; Senwanna, Chanokned; Khuna, Surapong; Lumyong, Saisamorn; Suwannarach, Nakarin (Frontiers in Cellular and Infection Microbiology, 2023)
Members of family Herpotrichiellaceae are distributed worldwide and can found in various habitats including on insects, plants, rocks, and in the soil. They are also known to be opportunistic human pathogens. In this study, twelve strains of rock-inhabiting fungi that belong to Herpotrichiellaceae were isolated from rock samples collected from forests located in Lamphun and Sukhothai Provinces of northern Thailand during the period from 2021 to 2022. Based on morphological characteristics, growth temperature, and multi-gene phylogenetic analyses of a combination of the internal transcribed spacer (ITS), the large subunit (nrLSU), and the small subunit (nrSSU) of ribosomal RNA, the new genus, Petriomyces gen. nov., has been found to accommodate the single species, Pe. obovoidisporus sp. nov. Additionally, three new species of Cladophialophora have also been introduced, namely Cl. rupestricola, Cl. sribuabanensis, and Cl. thailandensis. Descriptions, illustrations, and a phylogenetic tree indicating the placement of these new taxa are provided. Herein, we provide updates and discussions on the phylogenetic placement of other fungal genera within Herpotrichiellaceae.